How to Feed 311 Million of Indonesian People by 2050? Advancing Local Food Adaptation and Food Security Policy - Trisia, Marlisa Ayu; Osozawa, Katsuya; Bai, Hu (KnE Life Sciences, 2016)
During decades, rice production in Indonesia has continuously increased. However, the increase in food consumption is faster than the rate of production. The population growth in Indonesia is projected to grow by 24.5% over the next four decades, from 250 million in 2015 to 311 million in 2050. In addition, climate change impacts would also exacerbate food supply and endanger sustainable food production. If the food needs for the population cannot be met, Indonesia will become a food insecurity country. On the other hand, Indonesia has a great potential food supply from a local resource that can be developed as the basis for food security in the long-term period. However, those local food resources are not considered the main staple food although their production is not significantly influenced by climate. The advancing potency of local food adaptation can create climate-resilient agriculture to proceed national food security. In addition, effective governance is needed to implement policies which promote food availability, food accessibility and individual food utilization based on local resources. Keywords: Adaptation, food security, local food, policy